مستوى اليقظة الذهنية لدى أساتذة التعليم الإبتدائي - بغدادي بن داحة, سامية (كلية العلوم الاجتماعية, 2025)
هدفت الدراسة إلى التعرف على مستوى اليقظة الذهنية لدى أساتذة التعليم الابتدائي وكذلك التعرف عن الإستراتجية أكثر استخداما في ممارسة اليقظة الذهنية لدى الأساتذة ومعرفة أثر بعض العوامل الديمغرافية الجنس(الذكور، إناث)، الخبرة المهنية، المادة،المدرسة والمؤسسة التعليمية. ولتحقيق أهداف البحث تم استخدام المنهج الوصفي، طبقت على عينة من أساتذة التعليم الابتدائي قدر حجمها ب(60) أستاذا، اختيرت بطريقة عشوائية ولجمع البيانات تم استخدام مقياس العوامل الخمسة لليقظة الذهنية، إعداد BEAR et AL (2006) تعريب وتقنين البصري واخرين(2014) المتكون من (39) فقرة، وقد توصلت إلى النتائج التالية: • مستوى اليقظة الذهنية لدى أساتذة التعليم الابتدائي مرتفع . • الإستراتجية أكثر استخداما لدى الأساتذة التعليم الإبتدائي في ممارسة اليقظة الذهنية التصرف بوعي. • لا يوجد فروق ذات دلالة إحصائية في مستوى اليقظة الذهنية لدى أساتذة التعليم الإبتدائي تعزى لمتغير الجنس. • لا يوجد فروق ذات دلالة إحصائية في اليقظة الذهنية لدى أساتذة التعليم الإبتدائي تعزى لمتغير المادة المدرسة. • لا يوجد فروق ذات دلالة إحصائية في مستوى اليقظة الذهنية لدى أساتذة التعليم الإبتدائي تعزى لمتغير المؤسسة التعليمية. The study aimed to identify the level of mindfulness among primary school teachers, as well as to reveal the most commonly used strategies in practicing mindfulness among teachers, and to examine the impact of certain demographic factors, including gender (male, female), professional experience, subject, school, and educational institution. To achieve the research objectives, a descriptive approach was used. The sample consisted of 60 teachers, randomly selected. The researcher used the Five Factors of Mindfulness Scale, prepared by Bear et al. (2006) and adapted and standardized by Al-Basri et al. (2014). The scale consists of (39) items. The researcher reached the following results: • The level of mindfulness among primary school teachers is high. • The most commonly used strategy among primary school teachers in practicing mindfulness is to act consciously. • There were no statistically significant differences in the level of mindfulness among primary school teachers due to gender. • There are no statistically significant differences in the level of mindfulness among primary school teachers due to the variable of the subject taught. • There are no statistically significant differences in the level of mindfulness among primary school teachers due to the variable of the educational institution.
دراسة ميدانية ببعض إبتدائيات ماسرى ولاية مستغانم
Keywords: اليقظة الذهنية، أستاذ التعليم الإبتدائي